Perlindungan Hukum bagi Anak Usia Sekolah Terkait dengan Penyediaan Alat Kontrasepsi - Musfianawati, Musfianawati; Eka Adhining Tyas, Wahyu; Nazza Fauzi, Firda (JURNAL RECHTENS, 2025)
Article 103 paragraph 4 in PP No. 28 of 2024 concerning Health states the Provision of contraceptives for school-age children. The provision of contraceptives for school-age children is contrary to the principle of legal protection for children. Legal issues in this study: 1) Is the Provision of Contraceptives for School-Age Children Not Contrary to the Principle of Legal Protection for Children; 2) What is the Ratio Legis of the Regulations on the Article on the Provision of Contraceptives for School-Age Children in PP No. 48 of 2024 concerning Health. The purpose of this study is to determine and analyze the ratio legis and the regulation of the Provision of Contraceptives for School-Age Children Not Contrary to the Principle of Legal Protection for Children. This type of research is normative juridical. The results of the study are the ratio legis of PP No. 28 of 2024 concerning Health is to increase understanding and access for school-age and adolescents to reproductive health. Meanwhile, no additional explanation was found in Article 103 paragraph 4 point e regarding the provisions for the provision of contraceptives. If the focus is on those who are married, this is not in accordance with the category of the school age range that is allowed to marry. Meanwhile, if the focus is on education, it is less appropriate because the concept of provision means providing "physical goods" directly to school-age individuals. ABSTRAK Pasal 103 ayat 4 dalam PP No 28 Tahun 2024 tentang Kesehatan menyebutkan Penyediaan alat kontrasepsi bagi anak usia sekolah. Penyediaan alat kontrasepsi untuk anak usia sekolah bertentangan dengan prinsip perlindungan hukum bagi anak. Isu hukum dalam penelitian ini: 1) Apakah Penyediaan Alat Kontrasepsi Untuk Anak Usia Sekolah Tidak Bertentangan dengan Prinsip Perlindungan Hukum Bagi Anak; 2) Apa Ratio Legis Pengaturan Tentang Pasal Penyediaan Alat Kontrasepsi Bagi Anak Usia Sekolah pada PP No. 48 Tahun 2024 Tentang Kesehatan. Tujuan dari penelitian ini adalah Untuk mengetahui dan menganalisis ratio legis dan pengaturan Penyediaan Alat Kontrasepsi Untuk Anak Usia Sekolah Tidak Bertentangan dengan Prinsip Perlindungan Hukum Bagi Anak. Jenis penelitian ini yuridis normatif. Hasil penelitian adalah ratio legis dari PP No. 28 Tahun 2024 tentang Kesehatan adalah meningkatkan pemahaman dan akses bagi usia sekolah dan remaja terhadap kesehatan reproduksi. Sementara tidak ditemukan penjelasan tambahan dalam Pasal 103 ayat 4 poin e mengenai ketentuan penyediaan alat kontrasepsi. Jika fokus pada yang telah menikah, hal ini kurang sesuai dengan kategori rentang usia sekolah yang diperbolehkan menikah. Sementara jika fokus untuk edukasi kurang sesuai karena konsep penyediaan yang tersebut berarti memberikan “barang fisik” secara langsung kepada individu dengan usia sekolah Kata Kunci: Perlindungan Hukum; Anak Usia Sekolah; Alat Kontrasepsi